Hyper Space presents Another Dimension. - Hyper Space, Brussels; b-space.be, Brussels (Brussel : Hyper Space, 2000)
Delvoye, Wim ; Devriendt, Robert ; Fink, Christoph ; François, Michel ; Janssens, Ann Veronica ; Kasimir, Marin ; Rombouts, Guy ; Theys, Koen ; Tuerlinckx, Joëlle ; Venlet, Richard ; Vergara Santiago, Angel ; Byars, James Lee
curated by Marie-Puck Broodthaers
Hyper Space presents Another Dimension, Hyper Space, Brussels / b-space.be, Brussels, 8 December 2000 - 23 January 2001
boek